INFLUENCE OF CARTOON NETWORK ON THE ACQUISITION OF AMERICAN ENGLISH DURING CHILDHOOD - Poštič, Svetozar (Verbum, 2015)
This work tries to make a connection between English-language acquisition, especially reaching near-native pronunciation in American English, with cartoon-watching during childhood. The basis for the conclusion is found in the survey administered to eight first- and second-year Physics and Economics students at Vilnius University, Lithuania, who demonstrate a native-like speaking proficiency in American version of the English language. None of them have lived in an English-speaking country. In a questionnaire the students filled out, they were asked to assess which medium helped them most to learn the language, how much time they spent watching cartoons in their childhood, and which cartoons they watched most. They were also asked about their awareness of using certain lines from cartoons or films they watched, and about their identification with cartoon or film characters. The result proved the hypothesis that cartoon-watching is pivotal in reaching the near-native adoption of American English and the conclusion reached is that watching cartoons, combined with limited usage, is sufficient for such effective language acquisition. This link supports the findings of linguists that the chance of children reaching a near-native pronunciation of English is highest until the age of six, very small after the age of 13, and probable between those two ages. The students who were questioned watched American cartoons from early childhood to adolescence, and in that way improved their listening and speaking skills. After puberty, they complemented their writing and reading proficiency by using other media, most notably the internet.
Keywords: cartoons; Cartoon Network; second-language acquisition; English language; childhood